The Impact of Entrepreneurial Networking and Digital Marketing on MSMEs' Performance in East Kalimantan's Muslim Entrepreneurs' Culinary Sector - Norvadewi, Norvadewi; Parlina, Tika (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Small and Medium Enterprises play a strategic and important role in supporting the economic growth of developing and developed countries. The number of MSMEs in Indonesia is very large to support national income and create jobs The large number of MSMEs must be balanced with good performance in order to support the nation's economy with a contribution of almost one-third of national GDP. One factor that can improve the performance of MSMEs is entrepreneurial networking. Networking is a strategy for the development and expansion of new ideas and innovations. Through networking will open access and new business opportunities. Entrepreneurial networking or social networking usually serves as a means for MSMEs to overcome limited resources or capacity to go public. Entrepreneurial networking develops along with the development of information technology and the digital world which has an impact on marketing trends in the business world. Digital transformation will make MSMEs able to survive in the era of digital disruption and pandemic, so digital transformation for Indonesian MSME players is important.  This research is descriptive research with a quantitative approach. Data collection techniques using questionnaires and documentation. The population in this study is Muslim entrepreneurs in the culinary sector in East Kalimantan. Using the Slovin formula, a sample of 99 people was found. The sample determination uses purposive sampling. Data analysis techniques using Multiple Linear Regression analysis. The results showed that partially and simultaneously entrepeneurial networking and digital marketing had a significant effect on the performance of MSMEs in the culinary sector of Muslim entrepreneurs in East Kalimantan. MSMEs need to build professional, business and social networks that play a role in opening access to resources, knowledge and skills needed for the development and exploitation of new business opportunities and there needs to be a strengthening of social capital from both SMEs and the government for business development.  Digital marketing is an effective marketing strategy for MSMEs in the 5.0 era